Chemical Evolution Process and Quality Assessment of Seepage Groundwater in Tunnel Crossing Gas-Bearing Coal Seams. (16th May 2022) - Liu, Yuanming; Peng, Chen; Yuan, Qiaowei; Chen, Huiyu
Abstract : The chemical characteristics of groundwater in the gas coal seam section of the tunnel have rich geological significance. To study the chemical evolution process and controlling factors of groundwater in the gas-bearing coal seam section of the tunnel, and the influence of tunnel coal removal on the groundwater quality, field investigations and laboratory experiments were carried out on the groundwater in the coal measure strata and the high-gaseous section and surrounding aquifers. Through hydrochemical analysis, correlation analysis, hydrochemical simulation, and other methods, the chemical origin of groundwater in coal measure strata and other aquifers was revealed. The water quality of groundwater was analyzed by water quality index (WQI), sodium adsorption rate (SAR), percentage of soluble sodium (Na + %), and participation of sodium carbonate (RSC). The results show that the water samples of each aquifer are weakly alkaline. Influenced by formation lithology and mineral redox reactions, the genesis of coal formation water is more complex than that of natural karst groundwater. The water chemistry characteristics show obvious differences among aquifer groups, with low correlation of HCO3 -, Ca 2+, and Mg 2+ . The central drainage ditch is dominated by dolomite dissolution, and the sloping shaft side ditch is dominated by calcite dissolution, and ion exchange effects are prevalent in different water sources. In terms of irrigation water quality, the permeability index (PI), magnesium hazard (MH), and Kelly index (KI) calculations show that 45.8% of the water samples are in the "unsuitable" condition. This study helps to fully understand the quality of coal seam water in tunnels and can provide a reference for groundwater utilization.